Pelatihan Akuntansi pada Remaja bagi Siswa SMKN 1 Kota Tangerang - Trida Trida; Benjamin Melatnebar; Yopie Chandra (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
In the era of the digital economy, accounting is no longer merely a technical bookkeeping skill but a fundamental competence in financial literacy for the younger generation. Students of SMKN 1 Kota Tangerang, as prospective workers and entrepreneurs, are required to have a strong financial understanding to navigate industrial dynamics. This Community Service (Abdimas) activity aims to provide practical knowledge and expertise in accounting using a financial literacy approach. The implementation method involved intensive training, including lectures, interactive discussions, and Q&A sessions. The participants consisted of 70 students from the 10th and 11th grades of the Office Administration department. The results showed high enthusiasm from the participants, evidenced by two-way discussions regarding the phenomenon of cashless payments and the differences between investing and trading. Based on questionnaires completed by 57 respondents (81.4%), this training successfully shifted participants' paradigms in distinguishing between needs and wants, as well as the importance of long-term financial planning. It is concluded that applied accounting training bridges the gap between school theory and field practice, while equipping students with essential life skills to manage financial resources more responsibly and systematically.